2012
DOI: 10.1124/mol.112.079848
|View full text |Cite
|
Sign up to set email alerts
|

LYG-202 Augments Tumor Necrosis Factor-α-Induced Apoptosis via Attenuating Casein Kinase 2-Dependent Nuclear Factor-κB Pathway in HepG2 Cells

Abstract: Tumor necrosis factor-␣ (TNF-␣) is being used as an antineoplastic agent in treatment regimens of patients with locally advanced solid tumors, but TNF-␣ alone is only marginally active. In clinical use, it is usually combined with other chemical agents to increase its tumor response rate. Our previous studies reported that LYG-202 (5-hydroxy-8-methoxy-7-(4-(4-methylpiperazin-1-yl)butoxy)-2-phenyl-4H-chromen-4-one), a synthesized flavonoid with a piperazine substitution, has antiproliferative, antiangiogenic, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 59 publications
4
3
0
Order By: Relevance
“…In the present study, we showed that TNFα alone can induce the upregulation of CASP9 through a NF-κB-mediated FFL, but that it did not induce the apoptosis of the detected cells at the dose of 30 ng/mL. This observation was consistent with previous findings that low doses (10,20 or 50 ng/mL) of TNFα have no effect on cell survival [13,24,31]. NF-κB was therefore considered as having an anti-apoptotic role in TNFα signaling [10,11].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the present study, we showed that TNFα alone can induce the upregulation of CASP9 through a NF-κB-mediated FFL, but that it did not induce the apoptosis of the detected cells at the dose of 30 ng/mL. This observation was consistent with previous findings that low doses (10,20 or 50 ng/mL) of TNFα have no effect on cell survival [13,24,31]. NF-κB was therefore considered as having an anti-apoptotic role in TNFα signaling [10,11].…”
Section: Discussionsupporting
confidence: 93%
“…We also observed that TNFα significantly promoted the apoptosis of HeLa and HepG2 cells induced by DOX. This study, in conjunction with other observations [13,24,31], therefore indicated that TNFα can serve as a sensitizer to conventional chemotherapeutic agents to kill cancer cells by promoting their apoptosis. However, the molecular mechanism underlying this process remains unclear.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…(Cai et al, 1998;Jiang and Wang, 2004;Mohamad et al, 2005). Like the previous study (Schmelz et al, 2004;Xu et al, 2006;Chen et al, 2012), the HeLa and HepG2 cells induced by TNFa treatment did not subject to apoptosis in this study ( Figure S2). Like the previous study (Schmelz et al, 2004;Xu et al, 2006;Chen et al, 2012), the HeLa and HepG2 cells induced by TNFa treatment did not subject to apoptosis in this study ( Figure S2).…”
Section: Discussionsupporting
confidence: 76%
“…The cytochrome c released from mitochondria to cytoplasm initiate the activation cascade of caspases, which results in cell apoptosis (H€ uttemann et al, 2011;Sun et al, 2012). Like the previous study (Schmelz et al, 2004;Xu et al, 2006;Chen et al, 2012), the HeLa and HepG2 cells induced by TNFa treatment did not subject to apoptosis in this study ( Figure S2). However, the CYCS was upregulated by NF-kB in these TNFainduced cells.…”
Section: Discussionsupporting
confidence: 66%